VIRULENCE STATUS OF Phytophthora infestans (Mont.) de Bary IN WEST JAVA TO POTATO PLANTS THAT CONTAIN RB GENE - Hani Susanti; Rizkita Rachmi Esyanti; Eri Sofiari (Widyariset, 2013)
Phytophthora infestans (Mont.) de Bary causes late blight (LB) disease which can decrease potato (Solanum tuberosum L.) production up to 100%. RB gene as source of resistance to LB could be obtained from genetically modified potato cultivars with resistance genes from wild species Solanum bulbocastanum. Evaluation virulences of P. infestans to potato contain RB gene is an important step to know effectiveness of controlling this disease. The research was focussed on determining virulence status of the isolates to the transgenic and hybrid potato plants containing RB genes. Isolates were collected from Bandung, Cianjur, and Garut, were cultured on V8-agar medium at 18 ± 20C. Virulence test were performed using “detached leaves assay” method. Based on statistic analysis, the average leaf infected by LB in potatoes containing the RB gene was significantly lower than potatoes in control group. Results showed that 40,8% transgenic leaves and 54,5% hybrid leaves which containing RB gene attacked by LB , whereas the control group was infected 98,7%. The virulence level of P. infestans isolates from West Java on potato plants contain RB gene is still low compare to that in the control group.